Using Relational-cultural Theory to Negotiate Relational Rebuilding in Survivors of Intimate Partner Violence. Issue 2 (3rd April 2018) - Brown, Shanita; McGriff, Kashunda; Speedlin, Stacy
ABSTRACT: In this article, the authors describe the application of relational-cultural theory (RCT) for survivors of intimate partner violence (IPV). RCT's philosophical foundation and core processes work effectively within the context of the counseling session. Through the RCT lens, the authors examine how the theory's approaches can be utilized for relational rebuilding. Finally, RCT strategies are included for working with women who have experienced shame and relational disconnections as the result of IPV.